Secretome analysis of human schwann cells derived from malignant peripheral nerve sheath tumor. Issue 1 (28th October 2021) - Ferdoushi, Aysha; Jamaluddin, M. Fairuz B.; Li, Xiang; Pundavela, Jay; Faulkner, Sam; Hondermarck, Hubert
Abstract: Malignant peripheral nerve sheath tumors (MPNSTs) are highly aggressive, nerve‐associated tumors and the main cause of death amongst neurofibromatosis type I (NF1) patients. Schwann cells (SCs) are the pathogenic cell type in MPNST, however the secretome of human MPNST ‐derived SCs is poorly defined. In this study, a comprehensive proteomic analysis of the proteins secreted by the sNF96.2 human SC line, derived from a patient with MPNST, was performed using liquid chromatography‐tandem mass spectrometry (LC‐MS/MS). A total of 17, 354 unique peptides corresponding to 1538 individual proteins were identified. Among them, 995 proteins were confirmed as secreted using various bioinformatics tools including SignalP, SecretomeP, Vertebrate Secretome Database (VerSeDa), and Ingenuity Pathway Analysis (IPA). Gene Ontology and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment were conducted to assign protein localization and function, and to define enriched pathways. Protein binding was the most enriched molecular function, and the most enriched biological process was cell‐cell adhesion. Metabolic pathways showed the highest levels of enrichment. In addition, 13 of the identified proteins were validated in Western blotting. This comprehensive secretome map constitutes a reference library providing a new molecular insight into MPNST.